Mapping hierarchies of mobility in the Baikal Amur Mainline region: a quantitative account of needs and expectations relating to railroad usage - Sancho-Reinoso, Alexis; Saxinger, Gertrude; Fink, Christoph; Povoroznyuk, Olga; Wentzel, Sigrid Irene; Illmeier, Gertraud; Schweitzer, Peter; Krasnoshtanova, Natalia; Kuklina, Vera (Polar Geography, 2022)
The construction of railroad infrastructure in East Siberia and the Russian Far East was a key aspect of Soviet industrialization during the 1970s and 1980s. Although built primarily for freight transportation, the Baikal-Amur Mainline (BAM) and the Amur-Yakutsk Mainline (AYaM) have also been used for passenger transport and have thus contributed to increased mobility and heightened local expectations about future mobility. This article presents the results of an extensive survey carried out in the BAM/AYaM region, which maps experiences of individual mobility, including usage-related needs, practices, and expectations. The findings show low levels of satisfaction differing across the region’s social and spatial diversity. The paper argues that hierarchies of mobility prevail at two related levels in the BAM/AYaM region: 1) the state’s regional development policies favor industrial development, focusing on freight transportation while neglecting local passengers’ needs for improved individual mobility; and 2) intersectional structural conditions along lines of diversity, such as gender, age, ethnicity, and place of residence, result in mobility disadvantage and lower mobility satisfaction. These hierarchies are embedded in the broader social and spatial inequality structures in the Russian Federation.